Reciprocal matrices: properties and approximation by a transitive matrix - Bebiano, Natália (2022)
N. Bebiano: partially supported by project UID/MAT/00324/2019. R. Fernandes: partially supported by project UID/MAT/00297/2019. S. Furtado: partially supported by project UID/MAT/04721/2019.